Predictors of academic dishonesty among postgraduate students in South-West Nigeria (2019)
The university system is supposed to be in all sense of responsibility a place where there should be undiluted intellectualisation. This confers integrity on all spheres of life including students especially, postgraduate students. Anything to the contrary could lead to academic dishonesty. This study, therefore, investigates the prediction of self-control, attitude, motivation and perceived norm on academic dishonesty of postgraduate students in universities in Southwest Nigeria. These variables were measured with the following instruments: Academic Ethical Scale (r=0.93), Postgraduate Students Self-Control Scale (r=0.76), Postgraduate Students Attitude Scale (r=0.75), Postgraduate Students’ Motivation Scale (r = 0.76), and Postgraduate Students Perceived Norms Scale (r = 0.79). Using a sample of 200 postgraduate students from eight universities from the Southwest Nigeria, results showed that the four predicting variables significantly contributed to academic dishonesty of postgraduate students. However, motivation and attitude made the most contribution to the criterion measure. The findings and implications are discussed in the paper.